Pancasila dan Piagam Madinah, Pemersatu Masyarakat Majemuk: Sebuah Studi Perbandingan - Pamungkas, Doroteus Bryan Agung (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2017)
Diverse ethnic, religion, race, and culture have often been the reasons that people could not live side by side in harmony. The Nation-State of Indonesia founded on Pancasila as its way of life and ideology, seems to be in crisis.Some particular group, emerges from within Moslem society, makes any effort to found a state on the basis of Syariah Law. On the other hand, during his life time, the Prophet Mohammed seemed to praise highly the plural society. Even in Madinah he was struggling to protect peoples from diverse backgrounds. For the writer, Pancasila and the Madinah Charter could meaningfully have similar role for any plural society.